PENCEGAHAN HIV/AIDS MELALUI PENYULUHAN KESEHATAN REPRODUKSI PADA REMAJA DI DESA SIDAMUKTI BLOK CURUG - Lia Natalia; Yuyun Wahyu Indah Indriyani; Yeti Yuwansyah; Amelia Putri; Zahrotul Aini; Reninda Sari Salsabila (Sekolah Tinggi Ilmu Kesehatan (STIKes) Cirebon, 2023)
The number of cases of people with HIV AIDS is increasing from year to year. Adolescents infected with HIV AIDS in Indonesia show a number that tends to increase, triggered by ignorance of adolescents about reproductive health. Knowledge of how HIV AIDS is transmitted is very important to encourage youth to avoid HIV AIDS. It is hoped that empowering youth in building healthy lives, providing reproductive health counseling to adolescents, is expected to have an impact on reducing the incidence of HIV AIDS among adolescents. The purpose of the activity is to encourage young people to avoid HIV AIDS in Sidamukti village, Curug Block, Majalengka District, Majalengka regency which is able to provide health information to peers, especially about HIV and AIDS so that it will increase the knowledge of teenagers in the Curug block about reproductive health and the dangers of HIV AIDS. The type of activity carried out to overcome partner problems is by conducting reproductive health counseling to adolescents in the waterfall block of Sidamukti Village. The result of counseling from this activity is an increasing in adolescent knowledge about adolescent reproductive health.Keywords: Adolescent, HIV/AIDS, Adolescent Health CadresÂ Abstrak:Jumlah kasus penderita HIV AIDS semakin meningkat dari tahun ke tahun. Remaja yang terinfeksi HIV AIDS di Indonesia menunjukkan angka yang cenderung meningkat dipicu oleh ketidaktahuan remaja tentang kesehatan reproduksi. Pengetahuan cara penularan HIV AIDS sangat penting untuk mendorong remaja terhindar dari HIV AIDS. Pemberdayaan remaja dalam membangun hidup sehat penyuluhan kesehatan reproduksi pada remaja diharapkan dapat berdampak terhadap turunnya angka kejadian HIV AIDS di kalangan remaja. Tujuan kegiatan adalah mendorong remaja terhindar dari HIV AIDS di Desa Sidamukti, Blok Curug Kecamatan Majalengka Kabupaten Majalengka, yang mampu memberikan informasi kesehatan kepada teman sebaya khususnya tentang HIV AIDS sehingga akan meningkatkan pengetahuan remaja Blok Curug tentang kesehatan reproduksi dan bahaya HIV AIDS. Jenis kegiatan yang dilakukan untuk mengatasi permasalahan mitra adalah dengan melakukan melakukan penyuluhan kesehatan reproduksi pada remaja di Blok Curug Desa Sidamukti. Hasil penyuluhan dari kegiatan ini adalah meningkatnya pengetahuan remaja tentang kesehatan reproduksi remaja.Kata Kunci: Remaja, HIV/AIDS, Penyuluhan Kesehatan Remaja